Isotropic Scalar Quantum Sensing of Magnetic Fields for Industrial Application. Issue 8 (17th June 2020) - Staacke, Robert; John, Roger; Wunderlich, Ralf; Horsthemke, Ludwig; Knolle, Wolfgang; Laube, Christian; Glösekötter, Peter; Burchard, Bernd; Abel, Bernd; Meijer, Jan
Abstract: Magnetic field sensors based on quantum mechanic effects are often susceptible to misalignments of the magnetic field or need advanced procedures to compensate for these. Also, the record breaking sensitivities reported for superconducting quantum interference devices and alkali vapor magnetometers come along with large and complex experimental setups. The nitrogen vacancy center in diamond can be used to design a simple, small, and robust sensor without employing microwave radiation. By using compressed nanodiamond particles, it is possible to eliminate the need of an alignment of the magnetic field and still obtain the absolute magnetic flux density in a single measurement. In order to demonstrate the capabilities of this approach, a centimeter‐sized modified automotive demo board is employed as a complete sensor with a sensitivity of 78  μ T/ Hz . Abstract : As shown by the authors, the nitrogen vacancy center in diamond can be used to design a simple, small, and robust sensor without employing microwave radiation. Using compressed nanodiamond particles, it is possible to eliminate the need of an alignment of the magnetic field and still obtain the absolute magnetic flux density in a single measurement.